Neotectonic Activities and Quaternary Sedimentation in Parts of Jaipur Upland - Raghav, K S (Annals of Arid Zone, 2016)
The northern part of Jaipur upland comprising the catchment of the Mendha,Bandi, Kantli and Rupangarh river bears testimony to neotectonic activities.The basement induced post-Neogene tectonic adjustments are evidenced by a variety of morphotectonic and geological features. Study of the drainage net work along with torrace patterns of the river, disposition of erosional plains of Quaternary sedimentation etc. coupled with the neotectonic evidences recorded, signify that the post-Neogene tectonic adjustments have largely controlled the Quaternary sedimentation in this area.